The adventures of Dunno and his friends - Nosov, Nikolai Nikolaevich, 1908-; Laptev, A. (Alekseĭ Mikhaĭlovich), 1905-1965; Wettlin, Margaret (Moscow : Progress, 1980)
Relates the adventures of a group of Mites led by Dunno when their hot air balloon carries them far beyond their home in Flower Town.
Keywords: Voyages and travels -- Fiction